Monitoring steroid hormones in horses performing intense exercise loads - Zinovieva Svetlana; Kozlov Sergey; Markin Sergey (BIO Web of Conferences)
Performance of loads of different intensity and power by horses is accompanied by changes in the balance of metabolic processes provoked by the corresponding hormones. In this regard, the aim of the study was to evaluate the dynamics of changes in the level of steroid hormones when horses perform high-speed and speed-strength loads. The study involved 8 Russian trotters (6 stallions and 2 mares) of the running class 2.05 and faster, as well as 8 stallions of draft breeds (5 Soviet heavy draft breeds and 1 Vladimir breed, as well as 2 representatives of the Vyatka breed) prepared for testing under the heavy draft eventing program. Trotters performed a sweeping movement over a distance of 1600 m with a speed of more than 3 minutes. Draft horses trotted 2000 m with a traction force of 50 kg (heavy draft horses) and 30 kg (Vyatka stallions). The testosterone and cortisol levels were determined in the horses' blood taken before the start and after the finish. The data obtained showed that highspeed and high-speed-strength loads caused similar changes in the hormonal status of trotters and harness horses. The background and post-load testosterone levels in the horses' blood are more significantly affected by the length of the preliminary training than by the intensity and power of the load itself. Older and high-class trotters are capable of repeatedly increasing the level of cortisol in the blood in response to a high-speed (swinging) load. The muscle work performed by trotters and harness horses did not cause an imbalance of anabolic and catabolic processes in their bodies, which reflects the adequacy of the load presented to the current state of their training.